EXPLORING AGRI-PROJECTS’ RISKS AND OPPORTUNITIES IN A CHANGING CLIMATE: A CASE OF BLOEMFONTEIN, FREE STATE PROVINCE, SOUTH AFRICA - Bernard Moeketsi Hlalele (Journal CleanWAS)
Innovation is one of the most fundamental processes that underpins the economic growth and serves as an economic basis for developing solutions to socio-economic and environmental challenges such as climate change. Climate change has become one of the most threatening natural processes in the world, with major impacts in the economic development, this can also provide opportunities for new ventures. The aim of this study was to assess the climate change variability status in the study area to maintain businesses’ continuity, inform policy making for climate change risks adaptation and mitigation and set an avenue for climate change innovations entrepreneurship in the study area. Two drought indicators, Standardised Precipitation (SPI) and Reconnaissance Drought Indices (RDI) were used in quantifying drought events computed from monthly precipitation, minimum temperature and maximum temperature. Three temporal scales, seasonal (3) and annual (12) were selected for analysis for trend patterns using a Mann Kendall’s test. The trend analysis showed neither decreasing nor increasing statistically significant trends in all the selected scales expect in spring (Aug-Oct). This condition could imply that businesses can play defensive and diversification strategies to stay in the market. The results also present opportunities such as drought -resistant cultivars production for farmers.